2010
DOI: 10.1097/hpc.0b013e3181d24549
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Guidelines for the Management of Patients With Chest Pain Through a Critical Pathway Approach Improves Length of Stay and Patient Satisfaction But Not Anxiety

Abstract: A critical pathway can effectively and safely reduce LOS, increase patient satisfaction, and improve adherence to the guidelines for managing patients with chest pain. Anxiety is not statistically significantly reduced by this intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
11
0
4
Order By: Relevance
“…This result was in consistent with a previous study's findings which demonstrated that anxiety and uncertainty were significantly reduced after participants completed an online education intervention, after undergoing cervical disc herniation surgery [11]. Another study examining patients with chest pain demonstrated that a clinical schedule positively influenced patient's length of stay and satisfaction; however, patient's anxiety was not significantly reduced post-intervention [34]. Another study addressing adult cancer patients showed that the clinical schedule could support cancer caring to assess and manage patient's anxiety and depression [35].…”
Section: Discussionsupporting
confidence: 91%
“…This result was in consistent with a previous study's findings which demonstrated that anxiety and uncertainty were significantly reduced after participants completed an online education intervention, after undergoing cervical disc herniation surgery [11]. Another study examining patients with chest pain demonstrated that a clinical schedule positively influenced patient's length of stay and satisfaction; however, patient's anxiety was not significantly reduced post-intervention [34]. Another study addressing adult cancer patients showed that the clinical schedule could support cancer caring to assess and manage patient's anxiety and depression [35].…”
Section: Discussionsupporting
confidence: 91%
“…Other authors have reported that guideline-based standardized care in patients with acute myocardial infarction is associated with considerably lower mortality, shorter hospital length of stay, and lower healthcare cost [5,6]. Early reperfusion strategies including the initiation of fibrinolysis and/or transfer to an appropriate PCI-capable or non-PCI-capable center are among the most important factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the impact of clinical observation or clinical diagnosis units, particularly chest-pain units. [5][6][7][8][9][10][11][12][13][14][15] Studies of hospitalist-run units suggest shorter LOS in the entire hospital, 16 or in the target unit. 17 Although one study suggested a lower 30-day readmission rate, 18 most others did not describe this effect.…”
Section: Discussionmentioning
confidence: 99%